Fine-Tuning the Sonic Color-line: Radio and the Acousmatic Du Bois. Issue 1 (March 2015) - Stoever, Jennifer Lynn
<x xml:space="preserve">Abstract</x> In this essay, I perform archival work on W. E. B. Du Bois's little known history with American radio in tandem with literary analysis to rethink how we have understood The Souls of Black Folk (1903) and Dusk of Dawn (1940) as sonic texts. First, I re-examine 'the Veil', Du Bois's famous conception of the color-line in Souls, as an acousmatic device, an aural epistemology dependent on deliberately masking the source of one's voice to avoid the distortion caused by visual representation. Then, I contextualize Du Bois's second autobiographical work, Dusk of Dawn, within early 1940s radio culture in the U.S.A., more specifically the emergence of colorblind discourse developed alongside dominant understandings of radio as an acousmatic medium masking race. In Dusk of Dawn, Du Bois moves away from the color-line, a linear and visual metaphor, to the vacuum chamber, a more complex, diffuse, and aural figuration and, I argue, a sonic metaphor borrowed from his frustratingly racialized experiences with radio in an increasingly segregated United States. Exploring Du Bois's shifting theorizations of race and its expressions through acousmatic sound allows us to place segregation at the heart of the modernist rhetoric of technological innovation and understand how the 'sonic color-line' functioned as an important dynamic of the so-called 'Golden Age' of American broadcasting.